Fine-scale assessment of genetic diversity of trembling aspen in northwestern North America. Issue 1 (December 2016) - Latutrie, Mathieu; Bergeron, Yves; Tremblay, Francine
Abstract Background In North America, the last ice age is the most recent event with severe consequences on boreal species' ranges. Phylogeographic patterns of range expansion in trembling aspen (Populus tremuloides ) suggested that Beringia is likely to be a refugium and the "ice-free corridor" in Alberta may represent a region where small populations persisted during the last glacial maximum (LGM). The purpose of this study was to ascertain whether the origins of trembling aspen in western North America are reflected in the patterns of neutral genetic diversity and population structure. A total of 28 sites were sampled covering the northwestern part of aspen's distribution, from Saskatchewan to Alaska. Twelve microsatellite markers were used to describe patterns of genetic diversity. The genetic structure of trembling aspen populations was assessed by using multivariate analyses, Mantel correlograms, neighbor-joining trees and Bayesian analysis. Results Microsatellite markers revealed little to no neutral genetic structure ofP. tremuloides populations in northwestern North America. Low differentiation among populations and small isolation by distance (IBD) were observed. The most probable number of clusters detected by STRUCTURE was K = 3 (∆K = 5.9). The individuals in the populations of the 3 clusters share a common gene pool and showed a high level of admixture. No evidence was found that either Beringia or the "ice-free corridor" were refugia. Highest allelic richness (AR) and lowest heterozygosity (Ho ) were observed in Alberta foothills of the Rocky Mountains. Conclusions Contrary to our hypothesis, our results showed that microsatellite markers revealed little to no genetic structure inP. tremuloides populations. Consequently, no divergent populations were observed near supposed refugia. The lack of detectable refugia in Beringia and in the "ice-free corridor" was due to high levels of gene flow between trembling apsen populations. More favorable environmental conditions for sexual reproduction and successful trembling aspen seedling establishment may have contributed to increase allelic richness through recombination in populations from the Albertan foothills of the Rocky Mountains.